Love/Power - DeValve, Michael J. (Critical criminology, 2017)
Love supplants power as it is often understood in contemporary justice practice, obliterating it utterly. What, then, fills the vacuum? How can justice hope to endure without any mechanism for coercion? By what mechanism can justice hope to function? This essay will explore briefly Foucault’s thought about power as it functions in contemporary criminal justice, but will then develop a theoretical foundation inspired by Simone Weil, as well as a practical guide for a power modality that is consonant with the creation and sustainment of a loving justice.